(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the problem of police`s preventive activity. It was found that preventive activity is a system of special measures, means, operations and actions regulated by the norms of the current legislation of Ukraine, which is implemented by specially authorized entities for the purpose of prevention, prevention and prevention of violations of the regime of legality, rights and freedoms of a person and a citizen in in various spheres of social life. It is argued that preventive activity in the National Police of Ukraine is characterized by a number of important features, namely: 1) it is a "mechanical" part of the phenomenon of prevention, which, within the framework of the work of the National Police, is one of the key directions of the work of the state authority, which affects the essence and content of its competence and powers; 2) preventive police activity is aimed at prevention, prevention and prevention of the most socially negative offenses of an administrative and criminal nature; 3) preventive activity of the NPU is ensured due to the possibility of using instruments of state coercion; 4) the need to implement a preventive direction of work affects the organizational and structural construction of bodies and units of the National Police of Ukraine. The specified aspects make it possible to say that the preventive activity of the police is mainly regulated by the norms of the administrative law of Ukraine, and therefore acts as an object of administrative and legal regulation.